A study on the factors that influence changes in Malaysian housing price indicators / Nurfaeezah Ruhaizad - Ruhaizad, Nurfaeezah (Faculty of Business and Management, 2011)
This study is focus on the changes of house price indicators in Malaysian. The first objective of this research is to study the relationship between the dependent and independent variables. Secondly, the objective is to determine the most dominant factors that contribute to the changes of house price indicators in Malaysia. Lastly the objective of this research is to propose some recommendations and suggestions in order to help the management to overcome the problem faced. All the objectives were using different method in analyze the result. For the first and second objectives, the researcher used multiple regression analysis in order to get the result. So, it shows that the regression analysis can prove the first and second objectives where the result shows that only one independent variable are significant with the dependent variable while the other two variables are insignificant. Then, the result of regression analysis also has shown the most dominant factor that contributes to the changes of house price indicators. It shows that the income per capita is the only variable that significant and the most contribute to the changes of house price indicators in Malaysia. In addition, to test the fourth hypotheses, the researcher using the descriptive analysis to know the differences whether Malaysian people know or not the changes of house price indicators. Then, after the research done, the researcher can know that all the hypotheses can be proven and the excellent analysis about the result of regression can be made.